Active control of nonlinear coupled transient vibrations of multifunctional sandwich plates with agglomerated FG-CNTs core/magneto-electro-elastic facesheets. (October 2022) - Mahesh, Vinyas
Abstract: This article investigates the controlled nonlinear transient response of sandwich plates made of magneto-electro-elastic (MEE) facesheets and agglomerated carbon nanotube (ACNT) core. The control is achieved by active constrained layer damping (ACLD) treatment which consists of piezoelectric (PE) and viscoelastic (VE) layers. The agglomeration is mathematically modelled using the Eshelby–Mori–Tanaka approach. The governing equations are derived under the framework of finite element (FE) methods using Hamilton's principle and condensation technique. The VE patch of the ACLD treatment is modelled through the Golla–Hughes–McTavish method. This evaluation has considered two states of agglomerations, such as complete and partial agglomeration. The proposed FE model facilitates the integration of the three-field (magnetic, electric and elastic) coupling with the agglomeration and electromagnetic circuit effects, which makes this work interesting. It acts as a ready tool for the realistic design of a smart structure and system. In addition, the computational efforts and efficiency of the proposed FE model prove to be better than the commercial numerical software. Extensive numerical examples are solved to assess the influence of CNT distributions, electromagnetic circuits, coupling, mechanical boundary conditions, thickness configuration and ACLD patch position. This work serves as a novel benchmark solution for further research on the active control of agglomerated CNT structures. Highlights: The active control of sandwich plates with agglomerated CNTs and magneto-electro-elastic facesheets have been dealt for the first time. The influence of coupled fields on the damped vibrations are studied. Two states of agglomeration such as complete and partial are considered for evaluation. Also, the influence of electromagnetic loads are evaluated.